2021
DOI: 10.3390/vaccines9030265
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Competition Modulates Antibiotic Resistance in the Pre-Vaccination Era: A Modelling Study

Abstract: The ongoing emergence of antibiotic resistant strains and high frequencies of antibiotic resistance of Streptococcus pneumoniae poses a major public health challenge. How and which ecological and evolutionary mechanisms maintain the coexistence of antibiotic resistant and susceptible strains remains largely an open question. We developed an individual-based, stochastic model expanding on a previous pneumococci modelling framework. We explore how between- and within-host mechanisms of competition can sustain ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…Our analysis provides new insight into 'evolutionarily optimal' vaccine design, complementing a body of work trying to understand how genetically diverse pathogen populations respond to vaccination [70][71][72][73]. Our work shows that the dominant order LD is generally indicative of how many antigens are required to generate a strongly protective immune response.…”
Section: Multilocus Models and Vaccinationmentioning
confidence: 77%
See 1 more Smart Citation
“…Our analysis provides new insight into 'evolutionarily optimal' vaccine design, complementing a body of work trying to understand how genetically diverse pathogen populations respond to vaccination [70][71][72][73]. Our work shows that the dominant order LD is generally indicative of how many antigens are required to generate a strongly protective immune response.…”
Section: Multilocus Models and Vaccinationmentioning
confidence: 77%
“…Understanding how genetically-diverse pathogen populations respond to vaccination has been a focus of recent work [63][64][65][66]. Our analysis provides some insight into 'evolutionarily optimal' vaccine design, as the type of LD present is generally indicative of how many antigens are required to generate a strongly protective immune response.…”
Section: Multilocus Models and Vaccinationmentioning
confidence: 99%
“…Increases in erythromycin MICs were observed between 2001-2007 in Massachusetts despite a decline in antimicrobial prescriptions [45,46]. Furthermore, rates of antibiotic consumption were poorly correlated with rates of country-specific resistance in a modelling study of pneumococcal resistance to penicillins and macrolides across 20 European countries [47]. The global spread of particularly successful pneumococci, driven by other evolutionary processes, may account for these discrepancies [23,48].…”
Section: Antimicrobial Usementioning
confidence: 99%
“…However, incorporating such features comes at the cost of intense computational demands and decreased interpretability of some results, due to the models' complexity. Nonetheless, IBMs have been previously used to simulate the spread of infectious diseases ( 19 22 ) and specifically to study the effects of NPIs and vaccination strategies against COVID-19 ( 23 30 ). For instance, previous studies have shown that prioritizing vaccination of the elderly could limit future deaths or quality-adjusted life year losses ( 31 ).…”
Section: Introductionmentioning
confidence: 99%